CAUSES OF PRIMARY AMENORRHEA AT TERTIARY LEVEL HOSPITAL - Jabeen, Sadaqat; Faisal, Mehnaz; Nisar, Maleeha (Journal of Ayub Medical College Abbottabad, 2018)
Background: The objective of this study was to collect data of patients coming to us with primary amenorrhea. Finding the different causes of this problem and managing them accordingly with the help multidisciplinary team. Methods: In this descriptive case series, patients with primary amenorrhea coming to the Gynae A Unit, Lady Reading Hospital, Peshawar from December 2012 till September 2016 were included. Data was collected on predesigned proforma. Investigations were advised according to the protocol made by our unit. Data was analysed using SPSS version 16. Results: Total number of primary amenorrhea cases were 82. Forty-nine (59.8%) were unmarried and 33 (40.4%) were married. The mean age of the sample was 16±5.3 years. In 20 (24%) cases, there was gonadal dysgenesis. Mayer Rokistansky Kuster Hauser syndrome was found in 18 (21.9%) of cases. Constitutional and Turner syndrome in 11 (13.4%), respectively. Imperforate hymen in 7 (8.5%), vaginal septum in 5 (6.1%), swyer syndrome 2 (2.4%). Endometrial receptor deficiency in 4 (4.8%) cases. There were two cases of hypogonadotrophic hypogonadism. One case of hypothyroidism and one case of congenital adrenal hyperplasia (CAH). Conclusion: Gonadal dysgenesis was the most common cause as compared to Mullerian duct abnormalities. Patients with endometrial receptor deficiency were more challenging. Primary amenorrhea is a distressing problem for patients as well for parents. These people are misdiagnosed and mismanaged at various occasions. Keywords: Primary amenorrhea; gonadal dysgenesis; Swyer syndrome; Mayer Rokistansky; Kuster Hauser syndrome; congenital adrenal hyperplasia (CAH)